2016
DOI: 10.3855/jidc.7513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the immunogenic property of NT H. influenzae protein D with Neisseria meningitidis OMV in BALB/c

Abstract: Introduction: Identifying ideal non typeable Haemophilus influenzae (NTHi) vaccine candidates has not been easy due to extensive sequence and antigenic variation among gene products interacting with the immune system. Protein D (PD) is a highly conserved 42 kDa surface lipoprotein available in all H. influenzae, including NTHi. Methodology: In this study, the gene encoding PD was cloned from H. influenzae and expressed in Escheriachia coli TOPO10 cell in pBAD vector. Arabinose was used to express recombinant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…COPD as a major public health problem is mostly observed in newborn infants and one third of children will be expected to die per year, by 2020 from this devastating disease (11). Due to the loss of protective capsules in non-capsular strains, as well as the presence of variable phenotypes and genotypes, effective and potent vaccine against NTHi strains is not available yet, and according to reports of aggressive diseases and increased drug resistance against these strains, it seems necessary to make an effective vaccine against these strains (9,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COPD as a major public health problem is mostly observed in newborn infants and one third of children will be expected to die per year, by 2020 from this devastating disease (11). Due to the loss of protective capsules in non-capsular strains, as well as the presence of variable phenotypes and genotypes, effective and potent vaccine against NTHi strains is not available yet, and according to reports of aggressive diseases and increased drug resistance against these strains, it seems necessary to make an effective vaccine against these strains (9,12).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, OMVs can be considered as a new candidate for a vaccine. Due to the presence of various compounds, such as outer membrane proteins, lipopolysaccharide, peptidoglycan and the recent discovery of DNA and RNA in the OMV structure, it can be stated that OMV is a carrier of several native bacterial antigens and is therefore important for the development of the vaccine (9,19). The significant properties of membrane antigens and their surface exposure in OMV have led to the confirmation of structural, physicochemical stability and the protective and genomic properties of OMV in many bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another exosome-based vaccination approach to combat the influenza virus includes EVs released by gram-negative bacteria, which are referred to as outer membrane vesicles (OMVs) (157). Several recent studies have reported that OMV-derived vaccines can induce strong immune protection against the influenza virus in vivo (158)(159)(160)(161).…”
Section: Exosome-based Vaccines For Treatment Of Viral Infectious Diseasesmentioning
confidence: 99%
“…The interaction between H. influenzae and the immune system is occurred by the binding of IgD to its surface[ 56 ]; this interaction is shared with Moraxella (Branhamella) catarrhalis with unknown reasons. All 127 H. influenzae strains, including encapsulated serotypes a–f and NTHi, have this antigenically conserved 42-kDa protein[ 57 ], making it an attractive vaccine candidate. A 1092 bp open reading frame of hpd encodes a 364-amino acid protein.…”
Section: Introductionmentioning
confidence: 99%